2017
DOI: 10.26740/jepk.v2n2.p251-262
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kewirausahaan Melalui Variabel Intervening Teori Perilaku Terencana Terhadap Intensi Berwirausaha Mahasiswa Fakultas Keguruan Dan Ilmu Pendidikan Universitas Jember

Abstract: ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh pendidikan kewirausahaan terhadap intensi berwirausaha mahasiswa melalui pendekatan teori perilaku terencana. Apakah sikap berwirausaha, norma subjektif, dan kontrol perilaku mengintervening pendidikan kewirausahaan terhadap intensi berwirausaha mahasiswa. Penelitian yang dilakukan merupakan penelitian kuantitatif. Populasi dalam penelitian ini adalah mahasiswa S1 angkatan tahun 2011 di Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember tahun akademi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
2
2
0
6
Order By: Relevance
“…The results found that the value of b = 0.006 which means entrepreneurial attitude mediate the impact of entrepreneurial education on entrepreneurial intention. The results of this study supports previous study by Wibowo et al (2016); Cahyono (2014). It remarked that a good entrepreneurial attitude will increase student entrepreneurial intention.…”
Section: Hypothesis Testingsupporting
confidence: 91%
See 2 more Smart Citations
“…The results found that the value of b = 0.006 which means entrepreneurial attitude mediate the impact of entrepreneurial education on entrepreneurial intention. The results of this study supports previous study by Wibowo et al (2016); Cahyono (2014). It remarked that a good entrepreneurial attitude will increase student entrepreneurial intention.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Schools must be able to evaluate whether the entrepreneurial education programs provided to students are in accordance with the knowledge, skills and attitude competencies needed to create economic value activities from the products produced. The results of the study are in line with the previous study by Cahyono (2014) which mentioned that there is no relationship between enterpreneurial education and enterpreneurial intention. Similarly, other findings were stated by Lorz et al (2011); Bae et al (2014) revealed indifference result.…”
Section: Hypothesis Testingsupporting
confidence: 90%
See 1 more Smart Citation
“…Penelitian sebelumnya oleh Arie Eko Cahyono (2014), dalam penelitiannya yang Berjudul Pengaruh Pendidikan Kewirausahaan Melalui Variabel Intervening Teori Perilaku Terencana Terhadap Intensi Berwirausaha Mahasiswa Fakultas Keguruan Dan Ilmu Pendidikan Universitas Jember. Koefisien jalur dari variabel pendidikan kewirausahaan terhadap intensi berwirausaha mahasiswa FKIP Universitas Jember diperoleh skor pengaruh langsung sebesar 0,30 dengan arah positif, yang berarti bahwa semakin baik pendidikan kewirausahaan semakin baik intensi berwirausaha mahasiswa FKIP Universitas Jember.…”
Section: Tabelunclassified
“…Entrepreneurship-based education is the process of learning to instill entrepreneurial values through habituation and maintenance of behavior and attitudes (Kurniawan, 2014). Entrepreneurship education is an attempt to learn about the values, abilities and behavior of a person and one's behavior in creation and innovation (Cahyono. 2014).…”
Section: Introductionmentioning
confidence: 99%